LEGALITAS PEMBERIAN SUAKA TERHADAP EDWARD SNOWDEN OLEH RUSIA - Devi Asprilla; Ayub Torry Satrio Kusumo (Faculty of Law Universitas Sebelas Maret, 2016)
The objective of this research is to analyze the conformity of Russia’s action in granting asylum toward Edward Snowden and principles of asylum in international law. The type of legal research used by the author is normative legal research with the conformity of Russia’s action in granting asylum toward Edward Snowden and normative aspects of international law which consist of concepts and principles of asylum which are regulated in various international instruments related to asylum as the object of the study. This research is an analytical research with statue and conceptual approach which sources is using primary, secondary, and tertiary legal materials. The result of the research shows that Russia’s action in granting asylum toward Edward Snowden is legal and in conformity with the principles of asylum in international law despite the fact that the asylum granted toward him is temporary.